2004
DOI: 10.1124/jpet.103.061671
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of a New Major Intestinal CYP3A Form, CYP3A62, in the Rat

Abstract: Based on information of the nucleotide sequence obtained from rat genome clones, a new CYP3A (CYP3A62) cDNA was isolated from the cDNA library of a rat liver. The CYP3A62 cDNA was 1746 base pairs (bp) in length, which included 1491 bp of an open reading frame and 93 bp and 209 bp of the respective 5Ј-and 3Ј-noncoding regions. Amino acid sequence deduced from CYP3A62 cDNA shared the highest similarity with rat CYP3A9 (79.9%) among human and rat CYP3A forms previously reported. CYP3A62 mRNA and protein were cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(68 citation statements)
references
References 35 publications
(41 reference statements)
4
63
1
Order By: Relevance
“…This finding is consistent with data published by Matsubara et al (2004), Takara et al (2003), and Takemoto et al (2003) showing decreasing expression of CYP3A mRNA and decreasing activity along the whole intestine. Even for the human equivalent CYP3A4 declining mRNA expression and activity profile along the human intestine could be demonstrated (Thummel et al, 1997).…”
Section: Mitschke Et Alsupporting
confidence: 83%
“…This finding is consistent with data published by Matsubara et al (2004), Takara et al (2003), and Takemoto et al (2003) showing decreasing expression of CYP3A mRNA and decreasing activity along the whole intestine. Even for the human equivalent CYP3A4 declining mRNA expression and activity profile along the human intestine could be demonstrated (Thummel et al, 1997).…”
Section: Mitschke Et Alsupporting
confidence: 83%
“…administration of CyA, the disposition kinetics of CyA was little changed by LTX treatment (LTX 8 mg W kg W day, p.o., for 3 weeks), presumably because the expression of mdr1 and CYP3A mRNAs in the liver did not change almost. Moreover, Matsubara et al 21) reported that the mRNAs and proteins of CYP3A1 and CYP3A2 were induced in the rat liver after the DEX treatment (100 mg W kg W day) for 3 days, while those of CYP3A62 and CYP3A9 were induced in the intestine. In this study, although we did not evaluate the eŠect of LTX treatment on the expression of CYP3A62 and CYP3A9, we believe that the in‰uence of LTX treatment on these proteins was slight, if any, because the CLtot value of CyA after the i.v.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse hepatic and small intestinal microsomes were prepared according to the method reported previously (Matsubara et al, 2004), separated by SDS-polyacrylamide gel electrophoresis, and transferred to a nitrocellulose membrane. The membrane was immunostained with the anti-CYP3A antibody (Kawano et al, 1987) and alkaline phosphatase-conjugated goat anti-rabbit IgG, and signals were visualized with 5-bromo-4-chloro-3-indolylphosphate and nitro blue tetrazolium.…”
Section: Methodsmentioning
confidence: 99%